Analysis and Design of a Multi Octave Circularly Polarized Monopole Antenna for UWB, X and Ku-Band Applications - Vanka, Saritha; Seedrala, Tanmayi; Rani Areti, Jhansi (International Journal of Engineering and Technology, 2018)
This work presents a circularly polarized, CPW-Fed multi band operating monopole antenna. The monopole antenna consists of three parasitic elements, along with a stub at ground for impedance matching. The parasitic elements so far accumulated have shown their excellence in increasing the impedance bandwidth over the 6-18GHz band. The antenna was carved on FR-4 epoxy substrate which result a copper clad laminated structure. The CPW-Fed monopole antenna exhibits excellent circular polarization levels in the frequency region 6-18GHz. The simulation resulted a Return loss of less than -10dB, with good axial ratio less than -3dB over entire band of interest. The simulation was carried out through HFSS microwave studio. The antenna measured values are in good correspondence to the simulated values. Â